Synergistic Effects of Fertilization on Maize Yield and Quality in Northeast China: A Meta-Analysis - Xiaoqi Gao; Lingchun Zhang; Yulin An; Shaojie Wang; Guozhong Feng; Jiayi Lv; Xiaoyu Li; Qiang Gao (Agriculture, 2025)
Northeast China is a key grain production region yet achieving coordinated improvements in maize yield and quality across diverse environments remains challenging. This study conducted a meta-analysis to evaluate maize yield and quality responses to chemical fertilizer inputs under varying natural (climate, soil) and anthropogenic (fertilization, planting) conditions. The results indicated that fertilizer application increased yield by 20.0%, and protein, fat, and starch contents by 12.6, 1.4, and 1.2%, respectively, compared to no fertilization. Yield response was highest under precipitation <450 mm and temperatures >7 °C, while protein and fat gains were favored by >600 mm precipitation and 5–7 °C temperatures. Soils with pH <6.5 and saline–alkaline properties supported greater yield gains, while brown and black soils promoted protein and fat accumulation, respectively. Moderate nutrient inputs (N 180–240, P2O5 75–120, K2O 90–135 kg ha−1) outperformed lower or higher levels in improving both traits, with planting density also affecting response magnitude. Yield gains were primarily driven by soil fertility, whereas quality improvements were influenced by climate and management. Moderate fertilization facilitated the simultaneous enhancement of yield and quality. Tailored nutrient strategies based on soil and climate conditions can support regional maize productivity and contribute to food security.